Deficiency of Vitamin D and Anemia among Pakistani Children with Early Childhood Caries: A Case-Control Study - Muhammad Zohaib Younus, Syed Mahmood Shah, Ujala Mushtaque, Sadaf Ali, Anum Khan Khasi, Yasir Raza (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Early childhood caries (ECC) are usually seen among malnourished children. Objective: The main objective of the study was to assess that the children with early-childhood caries have a higher frequency of anemia and low vitamin D as compared to controls. Material and Methods: A case-control study was conducted between 2020 and 2021. A total of 266 children were enrolled out of which 144 had early childhood caries and 122 were caries-free. Vitamin D, ferritin, and blood count tests were conducted. A questionnaire was filled out by the parents of the children. Results: The results revealed that 266 children were included in the study (ECC n= 144); the mean age was 40.8 ± 14.1 months. It was observed that those Children who had ECC had low vitamin D and hemoglobin as compared to controls. There was a significant difference between low hemoglobin (<110 g/L) and 25(OH) D < 50 nmol/L (P<0.001). Conclusion: The study showed that vitamin-D deficiency and anemia are more common among children with early childhood caries. Hence, the cause is still unknown. A complete detailed history of the diet of children with early childhood caries will help to identify the risk factors of vitamin D deficiency and anemia.